Biosynthesis And Characterization of Silver Nanoparticles Using Nutgrass Rhizome Extract (Cyperus rotundus L.) - Sulastri, Rosvita Hilbrida; Supardi, I Wayan; Rupiasih, Ni Nyoman; Kasmawan, I Gde Antha; Adnyana, I Gusti Agung Putra; Sandi, I Nengah (BULETIN FISIKA; Vol 25 No 1 (2024): BULETIN FISIKA February Edition, 2024)
Silver nanoparticles (AgNP) have been successfully synthesized using the rhizome extract of nutgrass (Cyperus rotundus L.). The method of synthesizing nanoparticles using biological materials, both microorganisms and plants, is called biosynthesis. The variation in the ratio of AgNO 3 solution and nutgrass rhizome extract in units of µL and mL were 2:10, 5:10, 10:10, 15:10, 20:10, and 30:10, respectively. The process of forming silver nanoparticles was observed and characterized by UV-Vis spectrophotometer, FTIR, and SEM. The synthesis ratio that gives optimal result is 20 µL : 10 mL. The obtained silver nanoparticles have characteristic including Surface Plasmon Resonance (SPR) wavelength of 456.50 nm and random-shaped particles with an average size of 31-40 µm. The function groups formed include O-H with a peak around 3456.59 cm -1 , a C-H group around 2391.93 cm -1 , an O=C=O group stretching around 1155.41 cm -1 , and the alkene group C=C bending with a peak at around 934.55 cm -1 .